The Effect of The Use of Sign Language in The RCTI “Seputar iNews Siang” News Program on The Deaf Level of Understanding in Gerkatin Bandung (Jurnal Komunikasi Pembangunan, 2021)
This study aims to determine the influence of the system of sign language in a news program “Seputar iNews Siang” in a private Indonesia channel, on the level of understanding among deaf.  The study was conducted on deaf people from a disabilities movement and organization called Gerkatin, Bandung. The averaged ages of informant is 20-30 years old and they have watched and are fond with the news program studies. In this study, the authors apply descriptive quantitative research methods with the correlation approach significantly influenced the understanding level of people with hearing loss with a percentage of 65.7% and rcount of 1.307 >  rtable of 1.984 translation states that H0 is rejected and H1 is accepted. In variable X this research is included in the good category, with the results of the percentage score of 79.23% and the Y presentation variable of 85.73% which is included in the very good category. The total population is 250 people. This article applied a purposive sample technique and obtained a sample size of 30 people. The results of the study showed that the use of the system of sign language in “Seputar iNews Siang”is effective”. This shows that the level of understanding of deaf people is sufficient.